Preserved cognitive functions with age are determined by domain-dependent shifts in network responsivity - Dávid Samu (Nature Portfolio, 2017)
Cognitive abilities change with age, but why some decline and some do not is not clear. Here, the authors use data from the Cam-CAN cohort to show that distributed, multi-component brain responsivity and default-mode deactivation supports and characterizes preserved cognition across the adult lifespan.